On the Interpretation of World Values Survey Trust Question: Global Expectations vs. Local Beliefs - Ritwik Banerjee (Institute for the Study of Labor (IZA), 2016)
How should we interpret the World Values Survey (WVS) trust question? We conduct an experiment in India, a low trust country, to correlate the WVS trust question with trust decisions in an incentivized Trust Game. Evidence supports findings from one strand of the fractured literature – the WVS trust question captures expectations about others' trustworthiness, though not always. We show that WVS trust question correlates with globally determined stable expectations but does not correlate with short term locally determined fluctuations in beliefs about trustworthiness. One implication of our study is that survey based methods may not be used to measure contextualized beliefs.
Keywords: C91; C92; D03; 330; corruption; social capital; belief; trust games